If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(x+4)+3=4+7+2x
We simplify the equation to the form, which is simple to understand
2(x+4)+3=4+7+2x
Reorder the terms in parentheses
+(+2x+8)+3=4+7+2x
Remove unnecessary parentheses
+2x+8+3=+4+7+2x
We move all terms containing x to the left and all other terms to the right.
+2x-2x=+4+7-8-3
We simplify left and right side of the equation.
0x=0
0=0
This equation is an identity, so all real numbers are solutions.
| -2(3-4x)=7(x+2) | | 0.60x+0.05(12-x)=0.10(-71) | | 33=5v+3 | | 25n=525 | | 4u^3+2u^2-2u+1=0 | | 0.60x+0.05(12-z)=0.10(-71) | | 3y-11=25 | | 8-6d-3+7d=4 | | 3x+5-7-2x=3 | | -2k^2+3k+9=0 | | A+6=-3 | | 5y-3-4y=1 | | 10x+3y=18 | | 3v+7=19 | | 2(a-4)=-3(2a+4) | | 5x-20=9x+10 | | -3b+10=4 | | (x+xy^2)dy+ydx-y^2dx=0 | | 28=5w+3 | | m=52 | | 11g-7=81 | | 7y-28y^3= | | 2x-0.8=-2.5 | | 11m=77 | | -2=-4/2(6)+b | | 12s^2-60s+75= | | 8h-3=5 | | 16x^6-64x^4-9x^2+36=0 | | -5f-6=4 | | 2x+3=.4x | | 5x^2-18x-75=0 | | 2(a-4)=2.3d+3 |